Potential of Cyanobacteria as biological agents to improve sweet corn (Zea mays saccharate) germination and growth - Sulistyowati Dwiwanti; Hartono Rudi; Tasrif Arifin; Purwani Jati; Wati Cheppy; Kasno Antonius (BIO Web of Conferences)
Climate change can reduce crop yields. Cyanobacteria (blue-green algae), play an important role in sustainable agriculture by increasing plant resistance to drought. These microorganisms improve soil fertility by fixing nitrogen and producing bioactive compounds that enhance plant growth. The study aims to determine the role of cyanobacteria in improving germination and growth of sweet corn. It evaluated 11 strains of cyanobacteria (S1-S11) isolated from soil and corn roots in Grobogan Regency, Central Java, for their effect on corn seed growth. The germination experiment was conducted using a Completely Randomized Design (CRD) with four replications, treatment of 11 cyanobacteria strains, and added Control (S0). Surface-sterilized corn seeds (20 per treatment) were placed in sterile Petri dishes lined with sterile rice paper and cotton fibre. The experiment continued with an in-planta test using tubes containing a nutrient solution to observe the consistency of seed growth during the vegetative stage. The parameters observed were seed germination, plant height, root length, number of roots, and the fresh weight of shoots and roots. The results showed that cyanobacteria S1, S6, S7, and S8 significantly increased the germination and growth of sweet corn, providing promise for increasing corn productivity, especially in upland areas.